Exposing information sharing as strategic behavior: power as responsibility and "Trust" buttons. Issue 10 (21st June 2016) - Bălău, Nicoleta; Utz, Sonja
Abstract: Online platforms' success depends on individual's information sharing (IS). However, previous research showed that "knowledge is power" is a default‐perception in organizations and that individuals share relatively unimportant information while keeping the important private information for themselves. Trust has also been identified as important enabler of IS. We examined the role of power construed as responsibility for others' outcomes and of a "Trust" button, a theory‐inspired technological feature, using a 2(Power construals: opportunity vs. responsibility) × 2(Buttons: "Like" vs. "Like‐or‐Trust") × 2(Information sharedness as within‐subjects factor; public, private) design. Findings showed that construing power as responsibility and "Trust" button's presence increased the sharing of private information; clicking behavior yielded insights into the underlying mechanisms. Theoretical and practical implications are discussed.